К вопросу обеспечения асимптотической устойчивости макропараметров технологического процесса - Пигнастый, Олег Михайлович (Дніпровський державний технічний університет, 2010)
Исследована устойчивость макро-параметров технологического процесса промышленного предприятия. Получена оптимальная функция управления отклонениями макро-параметров технологического процесса, обеспечивающая стабильность технологического процесса.

The stability of the macro parameters of the technological process of an industrial enterprise is investigated. An optimal control function for deviations of the macro parameters of the technological process is obtained, which ensures the stability of the technological process.
Of the asymptotic stability of macro parameters of the technological process
Keywords: тип производства; PDE-модели поточных линий; производственная линия; PDE-модель производства; массовое производство; незавершенное производство; балансовые уравнения; квазистатический процесс; технологический процесс; production line; PDE-model of production; balance equations; production management system; stochastic process; work in progress; kinetic equation; conveyor; subject of labour; production system; mass production; management system